Online Learning Satisfaction Analysis of the Faculty of Computer Science Using the Fuzzy Logic Method - Fadrial, Yogi Ersan; Ambiyar, Ambiyar; Fadhilah, Fadhilah; Syahril, Syahril; Novendra, Rizki; Sutejo, Sutejo (Jurnal Pendidikan MIPA, 2021)
Abstract: Online learning is learning that uses the internet network with accessibility, connectivity, flexibility, and the ability to bring up various types of learning interactions. Satisfaction is a person's feelings of pleasure or disappointment that arise after comparing his perceptions of the performance or results of a product and his expectations. Research on student perceptions of online learning is limited to aspects of teaching and learning, the ability of lecturers, facilities and infrastructure. To get results from the perception or opinion of a student from the level of satisfaction of online lectures, it can be done using the Mamdani Fuzzy logic method and for calculations using the Slovin formula.Keywords: technology, fuzzy logic, online learning, model. DOI: http://dx.doi.org/10.23960/jpmipa/v22i2.pp256-261